Water and wastewater calculations manual - Lin, Shundar (McGraw-Hill Education LLC., 2014)
Water and wastewater calculations manual, third edition, provides basic principles, best practices, and detailed calculations for surface water, groundwater, drinking water treatment, and wastewater engineering. The solutions presented are based on practical field data and the most current federal and state rules and regulations. Designed for quick access to essential data, the book contains more than 100 detailed illustrations and provides both SI and U.S. customary units.